Mineros en movimiento: patrones residenciales y cultura sindical en perspectiva comparada - Manky, Omar (2019)
One of the most important changes in the global mining industry has been the demise of the «mining town» model. For more than two decades it has been replaced by a «hotel» model, in which workers sleep while in the camp, leaving their families far from the mining settlement for several days. This article has three objectives. First, to put this transformation in the broader context of changes in the Latin American mining industry. Second, to summarize, based on my previous research, the ways this system has undermined the traditional strategies of Peruvian mining unions. Finally, to argue that, despite these transformations, workers are not merely passive actors in the new settings, but rather they have developed new forms of action, albeit with variations depending on the local and national contexts in which they occur.